Analisis Kualitas Media Promosi Terhadap Perkembangan Produk Tabungan Kotak Di Perumda BPR Bank Gresik - Yusfifa Nanda Maulida Pradana; Sukaris Sukaris (CERED Indonesia Institute, 2022)
Banks can be said to be the blood of a country's economy. Banks are part of the financial system and payment system of a country, even in the current era of globalization, banks are also part of the world's financial and payment systems. The bank has obtained a license to stand and operate from the monetary authority of a country, then the bank becomes the property of the public. The research method used by researchers in this study is a descriptive qualitative method approach. Researchers have data from informants / resource persons by conducting direct interviews with the management of Perumda BPR Bank Gresik. From the results of these interviews, it shows that the savings box customers from month to month have increased. This shows that the promotional media carried out by Perumda BPR Bank Gresik was successful by acquiring more and more customers from month to month as long as this savings box was introduced to the public.